Pengembangan Perangkat Pembelajaran dengan Pendekatan Kontekstual untuk Meningkatkan Kemampuan Bahasa Inggris Siswa - Nasution, Asrindah; Nurhayati, Nurhayati; Rahim, Rani (Universitas Batanghari Jambi, 2024)
This research aims to find out how to develop learning tools with a contextual approach that is feasible and effective. The learning tools developed are learning tools with a contextual approach. The subjects in this research were class XI students at SMK Negeri 5 Medan. This type of research is R & D research using the 4-D model. To see the suitability of the learning tools, it was obtained from 5 expert validation people. Meanwhile, to see the effectiveness of learning tools, it can be obtained from testing the learning tools. The trials were carried out twice. The first trial was carried out on 9 students consisting of 3 low ability students, 3 medium ability students, and 3 high ability students. Meanwhile, the second trial was carried out on class XI students consisting of 36 students. Based on the conclusions of the five experts, they stated that learning tools with a contextual approach were included in the good category and suitable for use. Meanwhile, based on the results of the trial, students' assessments of the learning tools in the first and second trials were in the very good category. Students' English skills increase with learning tools based on a contextual approach. So it can be concluded that developing learning tools with a contextual approach is feasible and effective for use with students.